Long-Range, Border-Crossing, Horizontal Axon Radiations Are a Common Feature of Rat Neocortical Regions That Differ in Cytoarchitecture - Johnson, Brett A.; Frostig, Ron D. (Frontiers in Neuroanatomy, 2018)
Employing wide-field optical imaging techniques supported by electrophysiological recordings, previous studies have demonstrated that stimulation of a spatially restricted area (point) in the sensory periphery results in a large evoked neuronal activity spread in mammalian primary cortices. In rats’ primary cortices, such large evoked spreads extend diffusely in multiple directions, cross cortical cytoarchitectural borders, and can trespass into other unimodal sensory areas. These point spreads are supported by a spatially matching, diffuse set of long-range horizontal projections within gray matter that extend in multiple directions and cross borders to interconnect different cortical areas. This horizontal projection system is in addition to well-known area-to-area clustered projections to defined targets through white matter. Could similar two-projection cortical systems also be found in cortical regions that differ in their cytoarchitectural structure? To address this question, an adeno-associated viral vector expressing GFP was injected as an anterograde tract tracer into granular somatosensory cortex (trunk area), dysgranular cortex (somatosensory dysgranular zone and extrastriate cortex), and agranular motor cortex. Irrespective of the injection site the same two projection systems were found, and their quantification revealed a close similarity to findings in primary sensory cortices. Following detailed reconstruction, the diffuse horizontal axon radiation was found to possess numerous varicosities and to include short, medium and long axons, the latter extending up to 5.2 mm. These ‘proof of concept’ findings suggest that the similarity of the two projection systems among different cortical areas could potentially constitute a canonical motif of neocortical organization.